Incidence trends of keratinocytic skin cancers and melanoma in Israel 2006–11. (1st January 2015) - Sella, T.; Goren, I.; Shalev, V.; Shapira, H.; Zandbank, J.; Rosenblum, J.; Kimlin, M.G.; Chodick, G.
Summary: Background: The incidence of melanoma and keratinocyte cancers (KCs) is rising worldwide. Squamous cell carcinomas (SCCs) and basal cell carcinoma (BCCs) are the most common of all cancers. Objectives: To determine trends in the incidence of melanoma, BCC and SCC among 1·7 million members of Maccabi Healthcare Services (MHS) from 2006 to 2011. Methods: Data on patients newly diagnosed with melanoma, SCC and BCC were collected from the MHS Cancer Registry and based on histology reports from the centralized pathology laboratory. Age‐specific and overall age‐adjusted European standardized rates were computed. Trends were estimated by calculating average annual percentage change (AAPC). Results: During the 6‐year study period, 16 079 patients were diagnosed with at least one BCC, 4767 with SCC and 1264 with invasive melanoma. Age‐standardized incidence rates were 188, 58 and 17 per 100 000 person years for BCC, SCC and melanoma, respectively. All lesions were more common among men and primarily affected the elderly. BCC rates were stable throughout the study period [AAPC −0·7%, 95% confidence interval (CI) −4·5 to 3·2], while the incidence of SCC increased significantly (AAPC 15·5%, 95% CI 2·6–30·0). In contrast, melanoma rates continuously decreased (AAPC −3·0%, 95%CI −4·5 to −0·1). Conclusions: The incidence of KC in Israel is high. The disparities in incidence trends between SCC, BCC and melanoma allude to their different aetiologies. These findings underscore the importance of continuous monitoring, education and prevention programmes in a growing high‐risk population.